Pengaruh pH Terhadap Penyisihan COD Pada Pengolahan Campuran Limbah Cair Tahu Dan Kotoran Sapi Secara Anaerob - Rahmi, Intan Sri; Andrio, David; Veronika, Nina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tofu wastewater and cow dung are a waste containing high concentrations of organic compounds COD is 3305 mg/L and 10730 mg/L . To minimize the environmental pollution caused by tofu wastewater and cow dung , the waste should be processed . Processing the right to treat high concentrations of organic waste is anaerobic processing . This study aims to determine the effect of pH on the rate and efficiency of COD in tofu wastewater and cow dung . The study was conducted by varying the pH in the range 4-5 ; 6-7 ; 8-9 . The results showed the largest total COD removal occurred in the reactor acidic ( pH 4-5 ) with allowance rate of 3354.7 mg / L / day and 69.8 % removal efficiency.Keywords: Anaerobic processes, cow dung, tofu wastewater, COD